THE EFFECT OF THE AUDIT COMMITTEE AND THE INDEPENDENT BOARD OF COMMISSIONERS ON FIRM VALUE WITH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE: (Empirical Study of Primary Consumer Companies on the Indonesia Stock Exchange for the 2018-2022 Period) - Herti Tambunan; Zulfa Rosharlianti (Transpublika Publisher, 2023)
Audit committees are the vanguards of financial oversight, ensuring that financial reporting is accurate and transparent. On the other hand, independent commissioners bring a wealth of external expertise to the boardroom, providing an additional layer of checks and balances. Their independence is instrumental in countering agency problems and enhancing decision-making processes. This study aims to examine the effects of audit committees and independent commissioners on firm value with financial performance as a moderating variable. The study utilizes a quantitative approach and employs associative methods. The type of data utilized in this research is secondary data. The data analysis method employed in this research includes panel data regression and Moderated Regression Analysis, utilizing the Eviews application version 10 and Microsoft Excel. The population for this study comprises primary consumer companies listed on the Indonesia Stock Exchange for the period 2018-2022. The data collection technique employed in this study was purposive sampling, resulting in a total of 25 research samples. The findings of the study indicate that the independent audit committee and board of commissioners collectively influence firm value. Individually, the audit committee shows no significant effect on firm value, whereas the independent board of commissioners does have a significant effect on firm value. Furthermore, the financial performance is found to moderate the relationship between the audit committee and firm value, while it does not have the capacity to moderate the relationship between the independent board of commissioners and firm value.